THE BALANCE OF EFFECTORY AND REGULATORY MEMORY CELL INTERACTIONS AS A BASE FOR PRODUCING OF STEADY IMMUNE TOLERANCE STATE AFTER ORGAN TRANSPLANTATION (ANALYSIS OF PROBLEM AT THE LIVER TRANSPLANTATION EXAMPLE) - S. D. Artamonov; D. A. Velikiy; N. A. Onischenko; L. V. Bashkina; A. O. Nikolskaya; M. E. Krasheninnikov; I. M. Ivanov (Вестник трансплантологии и искусственных органов)
In this article the main mechanisms and methods of immune tolerance producing under influence of different antigenic loads in organism were considered. It was shown that the state of steady tolerance was produced by making the balance of effectory and regulatory cell interactions into innate and adaptive immunities. But because of a high risk of transplant rejection at different methods of tolerance producing it is necessary to work out safe diagnostic and prognostic methods for controlling of an individual level and power tolerance stability.